An Analysis of Difficulties Faced by the Third Grade Students of SMP Santa Veronika Pekanbaru in Writing Descriptive Texts - Simbolon, Angelia; Supriusman, Supriusman; Erni, Erni (CV. Rayyan Dwi Bharata, 2025)
This study aims to identify and analyze the difficulties students face in writing descriptive texts. Using a qualitative method, data was collected through a Likert scale questionnaire and a written test involving 25 respondents at the Junior High School. Based on the analysis, it was found that students experience difficulties mainly in five aspects: content, organization, grammar, vocabulary, and mechanics. Factors influencing these difficulties include limited vocabulary, minimal understanding of text structure, lack of writing practice, and challenges with grammar. Additionally, students' lack of interest in writing also affects their writing outcomes. The study concludes that a teaching approach focusing on writing fundamentals and enhancing students' interest in writing is needed. Recommendations for teachers include providing continuous writing practice and supplying engaging support materials to address obstacles in writing descriptive texts.